Christ as the Telos of Life Moral Philosophy, Athletic Imagery, and the Aim of Philippians - Arnold, Bradley (Mohr Siebeck, 2014)
Christus als des Lebens. Moralphilosophie, athletische Symbolik und das Ziel des Philipperbriefs.
PublicationDate: 20140827
Keywords: New Testament -- Hellenism -- Paul and his Greco-Roman Context -- Paul and Ancient Philosophy -- Intersubjektivität -- Neues Testament -- Antike Philosophie -- Array